Transformation of Public Services of Village and Village Governments by Era Digital - Shelly Noer Anggraeni; Eny Haryati; Dian Ferriswara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the transformation of public services at the village and sub-district levels in the digital era, as well as identify factors that affect the existing service gap, such as limited human resources (HR), low digital literacy of village apparatus, and lack of supporting infrastructure. Although the central government has launched various digitalization programs, such as digital device assistance and human resource training, many villages still face obstacles in implementing technology-based services. This study uses a qualitative approach with case studies in several villages in Indonesia to explore the experiences of village officials and communities related to the digitization of public services. The results of the study show that the majority of village officials have difficulty operating digital technology due to lack of training and digital literacy, while limited infrastructure also hinders the optimization of internet-based services. Village communities who are increasingly aware of the importance of digitalization expect faster and more efficient services, but the digital divide is the main barrier. This research provides recommendations for village governments to increase the digital capacity of village apparatus through continuous training and strengthening digital infrastructure. Overall, the digitization of public services in villages has great potential to improve the efficiency and quality of services, but requires more attention to improving skills and technological facilities at the village level.